Wage Arrears and the Distribution of Earnings in Russia - Hartmut Lehmann; Jonathan Wadsworth (Institute for the Study of Labor (IZA), 2001)
The increase in wage inequality in Russia during its transition process has far exceeded the increase in wage dispersion observed in other European countries undergoing transition. Russia also has an extremely large incidence of wage arrears. We analyse to what extent wage arrears affect the wage distribution and measures of wage inequality in Russia. We present counterfactual distributions, derived from a variety of different methods, which suggest that conventional measures of earnings dispersion would be some 20 to 30 per cent lower in the absence of arrears. We then go on to show how wage gaps at various points in the pay distribution across gender, education, region and industry are influenced by a failure to allow for wage arrears. Using our counterfactual estimates we show, for example, that the median gender wage gap would be around twenty-five points higher than the actual gap that we observe. Similarly, the counterfactual ratio of mean graduate pay to mean pay of those with primary education is around twenty points lower than observed. We show that the parameters of the counterfactual wage distributions are very similar to the parameters of the observed wage distributions of those not in arrears. This means that for those wishing to study aspects of wage differentials and inequality in Russia, it may be feasible to use the subset of those not in arrears and still get close to the true population parameters.
Keywords: J6; 330; Wage arrears; earnings inequality; counterfactuals; transition economies; Lohn; Verbindlichkeiten; Zahlungsunfähigkeit; Lohnstruktur; Einkommensverteilung; Russland; Lohnrückstände